2004
DOI: 10.1111/j.1747-7379.2004.tb00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Asian Americans and Voting Participation: Comparing Racial and Ethnic Differences in Recent U.S. Elections

Abstract: This research assesses the significance of race and ethnicity in the participation of Asian Americans in recent U.S. elections. It reviews the major characteristics of the nonwhite, multiethnic population in recent census surveys and discusses the necessity for voting behavior research to address effects of international migration on eligibility issues in voting participation. Results from analyzing U.S. Current Population Survey Voter Supplement files, 1994–2000, indicate that Asian Americans' apparent defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
4
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 26 publications
3
70
4
1
Order By: Relevance
“…While the regression coefficients are consistently significant and positive, the strength of the associations estimated here is markedly less pronounced compared to those found in studies of participation by naturalized immigrants (Lien 2004;Brady et al 1995). In the case of voting, these effects diminish when controls for migration-related factors and embeddedness scores are introduced.…”
Section: Resources and Participationcontrasting
confidence: 54%
See 1 more Smart Citation
“…While the regression coefficients are consistently significant and positive, the strength of the associations estimated here is markedly less pronounced compared to those found in studies of participation by naturalized immigrants (Lien 2004;Brady et al 1995). In the case of voting, these effects diminish when controls for migration-related factors and embeddedness scores are introduced.…”
Section: Resources and Participationcontrasting
confidence: 54%
“…It also asks respondents to report on so-called migration-related factors which have been linked to participation such as language proficiency (Tam Cho 1999;Brady et al 1995;Uhlaner et al 1989), period of stay (de Rooij 2011). In addition, work by Lien (2004) and Bilodeau (2008) suggests that immigrants from countries with political systems similar to Italy should have higher rates of participation compared to others (de Rooij 2011;Lien 2004;Bueker 2005). Similarities in political systems are accounted for in this analysis using their Polity IV scores (Marshall et al 2011).…”
Section: Control Variablesmentioning
confidence: 98%
“…One reason for this outcome may be because researchers find that the influence of resources, the strongest predictors of voting behavior, are much less consistent for minority racial and ethnic groups (de la Garza 2004;Leighley 2001;Lien 2004). For example, in a study of electoral participation in the 2000 election, limited to five large metropolitan areas with large Asian communities.…”
Section: Asian-americans and Voting Participation In National Electionsmentioning
confidence: 93%
“…While a part of the differential in participation rates across different racial groups can be explained by uneven distribution in resources (Verba et al 1993;Wolfinger and Rosenstone 1980) or varying exposure to mobilization efforts (Rosenstone and Hansen 1993), Latinos and Asian Americans are distinguished from the rest of the electorate in terms of their political opportunities and incentives (e.g., DeSipio 1996). For instance, scholars have found that another set of variables due to their particular status as immigrant-majority and racialminority groups significantly affects their active participation in politics: for instance, length of residence and nativity (Bass and Casper 2001;Lien 2004;Ramakrishnan 2005), English proficiency (Cho 1999), the extent of acculturation (Lien 1994), experiences of discrimination (Schildkraut 2005), group consciousness (Leighley and Vedlitz 1999;Stokes 2003;Uhlaner et al 1989;Wong et al 2005), and religious or non-religious organizational membership (Diaz 1996;Jones-Correa and Leal 2001).…”
mentioning
confidence: 98%